Accelerated Diversification Explains the Exceptional Species Richness of Tropical Characoid Fishes - Melo, Bruno F. [UNESP]; Sidlauskas, Brian L.; Near, Thomas J.; Roxo, Fabio F. [UNESP]; Ghezelayagh, Ava; Ochoa, Luz E. [UNESP]; Stiassny, Melanie L. J.; Arroyave, Jairo; Chang, Jonathan; Faircloth, Brant C.; MacGuigan, Daniel J.; Harrington, Richard C.; et al. (Oxford University Press (OUP), 2022)
The Neotropics harbor the most species-rich freshwater fish fauna on the planet, but the timing of that exceptional diversification remains unclear. Did the Neotropics accumulate species steadily throughout their long history, or attain their remarkable diversity recently? Biologists have long debated the relative support for these museum and cradle hypotheses, but few phylogenies of megadiverse tropical clades have included sufficient taxa to distinguish between them. We used 1288 ultraconserved element loci spanning 293 species, 211 genera, and 21 families of characoid fishes to reconstruct a new, fossil-calibrated phylogeny and infer the most likely diversification scenario for a clade that includes a third of Neotropical fish diversity. This phylogeny implies paraphyly of the traditional delimitation of Characiformes because it resolves the largely Neotropical Characoidei as the sister lineage of Siluriformes (catfishes), rather than the African Citharinodei. Time-calibrated phylogenies indicate an ancient origin of major characoid lineages and reveal a much more recent emergence of most characoid species. Diversification rate analyses infer increased speciation and decreased extinction rates during the Oligocene at around 30 Ma during a period of mega-wetland formation in the proto-Orinoco-Amazonas. Three species-rich and ecomorphologically diverse lineages (Anostomidae, Serrasalmidae, and Characidae) that originated more than 60 Ma in the Paleocene experienced particularly notable bursts of Oligocene diversification and now account collectively for 68% of the approximately 2150 species of Characoidei. In addition to paleogeographic changes, we discuss potential accelerants of diversification in these three lineages. While the Neotropics accumulated a museum of ecomorphologically diverse characoid lineages long ago, this geologically dynamic region also cradled a much more recent birth of remarkable species-level diversity. [Biodiversity; Characiformes; macroevolution; Neotropics; phylogenomics; ultraconserved elements.]